On the Structure and Functions of the Czech Orthography - Ulicny, Oldrich; Kasparkova, Pavlina; Kurdikova, Magda; Vaclavkova, Katerina (Bohemica Olomucensia, 2016)
Principles of the Czech orthography can be observed in the relationship between phonemes and morphemes (Josef Vachek), or in the unified registration of the morpheme, regardless of the pronunciation in various co-occurrences, which is the basic orthographic principle governing especially the Slavonic writing systems (Baudouin de Courtenay). In this article, the authors describe the auxiliary character of the phonological principle, which supports merely the recording function of the orthography. On the other hand, the morphematic principle fulfils both basic functions of writing and orthography, i. e. recording and recognition of the meaning of morphs and words in a sentence. Moreover, in the Czech orthography, the specific principle of ligatures represent one third of Czech graphemes. From the synchronic viewpoint, the ligatures can be interpreted as cases of the morphematic principle. - Our conclusions are supported by an analysis of spelling skills of pupils, who tend to make the least errors and misspellings in writing morphemes, even if their pronunciation varies.
Keywords: orthography; script; Czech orthography; phonological principle; morphematic principle; ligature; misspeling